2020
DOI: 10.3389/fmicb.2020.01734
|View full text |Cite
|
Sign up to set email alerts
|

The Independent Biological Activity of Bacillus thuringiensis Cry23Aa Protein Against Cylas puncticollis

Abstract: The Cry23Aa/Cry37Aa proteins from Bacillus thuringiensis (Bt) have been described toxic to Cylas puncticollis larvae. In general, it is believed that Cry23Aa and Cry37Aa act jointly to exert the insecticidal activity, while there is no evidence of their toxicity individually. Therefore, in the present study, the contribution of each protein in the insecticidal activity toward C. puncticollis larvae has been assessed. The results showed that both proteins were toxic for C. puncticollis larvae when tested indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The Mpp23Aa/Xpp37Aa proteins were first described as a binary toxin based on the fact that both genes were located in the same operon. However, recently, it was shown that these proteins were toxic for C. puncticollis larvae when tested individually [ 36 ]. In our study, we have tested the toxicity against A. grandis larvae by using a B. thuringiensis strain that expresses both proteins; thus, we cannot determine whether both proteins are required to exert their toxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The Mpp23Aa/Xpp37Aa proteins were first described as a binary toxin based on the fact that both genes were located in the same operon. However, recently, it was shown that these proteins were toxic for C. puncticollis larvae when tested individually [ 36 ]. In our study, we have tested the toxicity against A. grandis larvae by using a B. thuringiensis strain that expresses both proteins; thus, we cannot determine whether both proteins are required to exert their toxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Since insecticidal proteins tend to be moderately host specific, the first step in working towards a transgenic plant is to identify proteins active against SPW (Rukarwa et al 2013). Several proteins have been identified as toxic to SPW and it has been demonstrated that they could be used independently (Hernández-Martínez et al 2020;Prentice et al 2011). Although transgenic approaches are a routine and widely used component of other crop systems for insect control, similar to the case with a gene suppression strategy, it remains at an early stage for sweetpotato as effective SPW protein toxins or their requisite transgene expression is limiting (Morán et al 1998;Hernández-Martínez et al 2020).…”
Section: Transgenic Plantsmentioning
confidence: 99%
“…Several proteins have been identified as toxic to SPW and it has been demonstrated that they could be used independently (Hernández-Martínez et al 2020;Prentice et al 2011). Although transgenic approaches are a routine and widely used component of other crop systems for insect control, similar to the case with a gene suppression strategy, it remains at an early stage for sweetpotato as effective SPW protein toxins or their requisite transgene expression is limiting (Morán et al 1998;Hernández-Martínez et al 2020). Thus far, protein expression in the root has been minimal and has not had any significant effect on insect mortality (Rukarwa et al 2013).…”
Section: Transgenic Plantsmentioning
confidence: 99%
“…The other proteins (Mpp23 and Xpp37) can be found in the Bt parasporal body but show secondary structures different to other 3-domain Cry proteins. Both proteins were considered a binary toxin but their effect in a study with Cylas puncticollis was additive [17]. The Mpp23 and Xpp37 proteins were prepared from the EG10327 strain, which expresses Mpp23Aa1 and Xpp37Aa1, following Rodríguez-González et al [18].…”
Section: Introductionmentioning
confidence: 99%